Tumor-Induced Osteomalacia: Increased Level of FGF-23 in a Patient with a Phosphaturic Mesenchymal Tumor at the Tibia Expressing Periostin - Anke H. Hautmann; Josef Schroeder; Peter Wild; Matthias G. Hautmann; Elisabeth Huber; Patrick Hoffstetter; Martin Fleck; Christiane Girlich (Case Reports in Endocrinology)
In our case, a 45-year-old male patient had multiple fractures accompanied by hypophosphatemia. FGF-23 levels were significantly increased, and total body magnetic resonance imaging (MRI) revealed a tumor mass located at the distal tibia leading to the diagnosis of tumor-induced osteomalacia (TIO). After resection of the tumor, hypophosphatemia and the increased levels of FGF-23 normalized within a few days. Subsequent microscopic examination and immunohistochemical analysis revealed a phosphaturic mesenchymal tumor mixed connective tissue variant (PMTMCT) showing a positive expression of somatostatin receptor 2A (SSTR2A), CD68, and Periostin. Electron microscopy demonstrated a poorly differentiated mesenchymal tumor with a multifocal giant cell component and evidence of neurosecretory-granules. However, the resected margins showed no tumor-free tissue, and therefore a subsequent postoperative radiotherapy was performed. The patient is still in complete remission after 34 months. Tumor resection of PMTMCTs is the therapy of choice. Subsequent radiotherapy in case of incompletely resected tumors can be an important option to avoid recurrence or metastasis even though this occurs rarely. The prognostic value of expression of Periostin has to be evaluated more precisely in a larger series of patients with TIO.